2016
DOI: 10.1111/pai.12607
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood eosinophils in early infancy are predictive of atopic dermatitis in children with risk for atopy

Abstract: Elevated blood eosinophils at age 4 weeks have a predictive value for the onset of atopic dermatitis in infancy and early childhood in children with high risk for atopy. Early eosinophil counts may therefore be helpful for counseling parents to provide infant skincare but furthermore identify individuals for interventional trials aiming at allergy prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…On the contrary, BT did not play any diagnostic role in children with drug hypersensitivity . Supporting previous observations that EE had reflected the present atopic status, elevated EE at 4 weeks of age had a predictive value for the onset of AD at 7 months, 1, 2, and 3 years of age in a birth cohort with high risk for atopy . The chemokine CCL17 has been reported to correlate with the disease severity in infants suffering from AD sensitized against food or airborne allergens .…”
Section: Biomarkers Of Disease Severitysupporting
confidence: 77%
See 1 more Smart Citation
“…On the contrary, BT did not play any diagnostic role in children with drug hypersensitivity . Supporting previous observations that EE had reflected the present atopic status, elevated EE at 4 weeks of age had a predictive value for the onset of AD at 7 months, 1, 2, and 3 years of age in a birth cohort with high risk for atopy . The chemokine CCL17 has been reported to correlate with the disease severity in infants suffering from AD sensitized against food or airborne allergens .…”
Section: Biomarkers Of Disease Severitysupporting
confidence: 77%
“…49 Supporting previous observations that EE had reflected the present atopic status, 50 elevated EE at 4 weeks of age had a predictive value for the onset of AD at 7 months, 1, 2, and 3 years of age in a birth cohort with high risk for atopy. 51 The chemokine CCL17 has been reported to correlate with the disease severity in infants suffering from AD sensitized against food or airborne allergens. 52 Interestingly, this correlation was higher for patients sensitized to food allergens and CCL17 was found mainly in the (inflamed) skin but not in the gut.…”
Section: Biomarkers Of Disease Severitymentioning
confidence: 99%
“…Allergic diseases may share common mechanisms in the pathogenesis [25, 26]. In this regard, eosinophil plays a key role in the pathogenesis and development of atopic disease including asthma and eczema [14, 27]. Eosinophil secretes cytotoxic granules including major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil peroxidase (EPO), and eosinophil-derived neurotoxin (EDN) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil secretes cytotoxic granules including major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil peroxidase (EPO), and eosinophil-derived neurotoxin (EDN) [14]. Eosinophil granules contain a crystalloid core composed of MBP-1 and a matrix composed of ECP, EDN, and EPO [27]. MBP, EPO and ECP are toxic to a variety of cells and tissues, including heart, brain, and bronchial epithelium [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Dumas et al [28] analyzed the prospective data of 921 hospitalized children with bronchiolitis in 17 centers in the United States, and found that the risk of recurrent wheezing was signi cantly increased in children with eczema. It has been con rmed that eosinophils play a key role in the pathogenesis and development of atopic diseases including asthma and eczema [29,30] . Accordingly, one study [31] reported that recurrent wheezing at 36 months after bronchiolitis in infants was associated with eosinophilia.…”
Section: Discussionmentioning
confidence: 99%